"Humanum ignoscere est". The relationship of national and supranational identifications with intergroup forgiveness. (15th January 2017) - Hamer, Katarzyna; Penczek, Marta; Bilewicz, Michał
Abstract: There is mixed evidence on the role of national identification in intergroup forgiveness after historical crimes. We propose that this is due to the dual character of national identification, which consists of a general sense of belonging (shared with supranational identifications) and a more specific sense of distinctiveness. Study 1, performed on a Polish student sample ( N  = 314), showed that national identification decreases the level of intergroup forgiveness, when its shared variance with supranational identifications is partialled out. On the contrary, broader identifications (with all humanity, with the European Union) have clearly positive effects on intergroup forgiveness. Study 2 replicated these findings in a larger nationwide Polish sample ( N  = 1006) in the context of two groups of historical perpetrators (Germans, Russians) and explored the impact of supranational identifications on forgiveness to the groups who are not members of such shared categories (e.g. Russians not belonging to the category "European Union"). Both studies support the view that broad, supranational identifications – including both victims and perpetrators – are important individual difference antecedents of reconciliation and intergroup forgiveness. Highlights: Supranational identities are crucial individual difference predictors of forgiveness. We clarify mixed results upon the role of national identity in intergroup forgiveness. A dual character of national identity on forgiveness is shown. A general sense of belonging shared with supranational identities boosts forgiveness. A sense of national distinctiveness hinders forgiveness.